2021
DOI: 10.3390/math9233001
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Proinov-Type Fixed-Point Results in Non-Archimedean Fuzzy Metric Spaces

Abstract: Very recently, by considering a self-mapping T on a complete metric space satisfying a general contractivity condition of the form ψ(d(Tx,Ty))≤φ(d(x,y)), Proinov proved some fixed-point theorems, which extended and unified many existing results in the literature. Accordingly, inspired by Proinov-type contraction conditions, Roldán López de Hierro et al. introduced a novel family of contractions in fuzzy metric spaces (in the sense of George and Veeramani), whose main advantage is the very weak constraints impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…The results proved in this article generalized the results present in [26][27][28][29]. For some more related results, see [30][31][32][33][34].…”
Section: Remarksupporting
confidence: 78%
“…The results proved in this article generalized the results present in [26][27][28][29]. For some more related results, see [30][31][32][33][34].…”
Section: Remarksupporting
confidence: 78%
“…Following this development, Heilpern [3] employed the idea of the fuzzy set to initiate a class of fuzzy set-valued mappings and presented a fxed point(Fp) theorem which is a fuzzy version of the Fp result of Nadler [4]. Tereafter, a substantial number of authors have studied the existence of Fp of fuzzy set-valued maps, for example, see [5][6][7][8][9][10]. Following Zadeh [2], an intuitionistic fuzzy set (IFS) was brought up by Atanassov [11] as an additional refnement of the notions of fuzzy set.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Khojasteh et al [9] provided a novel approach to prove the existence of fixed point by exploring the concept of simulation functions, which exhibit a significant unifying power. Accordingly, many researchers extended and enriched this notion in various distinct metric spaces (see [11,14,[16][17][18]). In 2018, inspired by the aforementioned approach, Melliani and Moussaoui [8,19] proposed a new type of fuzzy contractions, called F Z-contraction in the context of fuzzy metric spaces and showed that this new form of contractions can also yield a unique point of view for various well-known concepts such as fuzzy contractions [5], fuzzy ψ-contractions [6], and fuzzy H-contractions [7].…”
Section: Introductionmentioning
confidence: 99%